Pembelajaran pada Masa Covid-19 di Kluet Tengah dan Kluet Timur - Samwil; Muzakkir; Said Fadhlain (Jurnal Sosiologi Agama Indonesia (JSAI), 2021)
This article aims to describe the implementation of online learning during the COVID-19 amid the lack of technological infrastructure available for educational institutions and the public in Kluet Tengah and Kluet Timur. This study uses an approach with a descriptive model. Data were obtained from interviews and relevant literature studies. The informants were selected using a purposive technique with specific considerations or criteria. The Covid-19 pandemic did not stop education and learning activities in Kluet Tengah and Kluet Timur. Students are still learning, and teachers are still teaching. However, the process of education and learning that takes place is very ineffective. There are many obstacles experienced by educational institutions, teachers, and students in carrying out learning activities, especially maximizing the learning process. The lack of facilities and technological infrastructure supporting the learning process makes learning effectiveness low.